Mechanisms structuring arboreal ant communities along ecological gradients in New Guinea rainforests - Plowman, Nichola Sarah (Jihočeská univerzita, 2018)
The thesis explores the community ecology and diversity of tropical ants, with a strong focus on the arboreal ants of Papua New Guinea rainforests. The aim was to investigate the drivers of community structure in these diverse communities, and how these change along the ecological gradients of elevation and forest succession. Using unique datasets from censuses of whole forest plots at low, mid and high elevation forests, the effects of vegetation structure and nest microhabitat use on ant community structure and diversity are compared across elevations. Furthermore, a community study of an understorey ant-plant mutualism was undertaken to explore elevational changes in interaction networks and the costs and benefits of mutualistic interaction. For lowland primary and secondary forest, taxonomic, functional and phylogenetic diversity of arboreal ant communities were quantified. In addition, aspects of the methodology of community functional diversity studies are examined, and suggested improvements to data handling in cases where full datasets are not available are discussed.
Mechanisms structuring arboreal ant communities along ecological gradients in New Guinea rainforests
Keywords: ants; Formicidae; New Guinea; tropical forests; elevation; succession; canopy; understorey; vegetation; ecological drivers; ecological gradients; ants; Formicidae; New Guinea; tropical forests; elevation; succession; canopy; understorey; vegetation; ecological drivers; ecological gradients